Effect of four weeks of calcium supplementation on plasma non-esterified fatty acids during a twenty five mile cycling time trial - Jawadwala, R.; Atkins, S.; Lowe, N. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
High calcium diets have shown to markedly inhibit lipogenesis (Xue et al., 1998) and accelerate lipolysis (Zemel et al., 2000). An in-vitro model suggesting the role of cAMP and phosphodiesterase 3B (Xue et al., 2001) has been implicated in the relationship between calcium and lipolysis. Recently the role of calcium sensing receptor in adipocytes has been shown to impact lipolysis via a similar mechanism (Youghan, et al., 2011). Increased lipolysis during endurance exercise may improve the availability of fat as an energy substrate, thus sparing glycogen. Therefore the objective of the current research was to investigate the effect of calcium supplementation on the availability of non-esterified fatty acids (NEFA) during a cycling time trial. Ten male well-trained cyclists (mean ± SD; age 35.8 ± 11.3 yrs, stature 176 ± 7.1 cm, body mass 73.8 ± 9.3 kg, O2peak 4.59 ± 0.8 l/min, Wpeak 350 ± 42 W) were recruited. Participants were tested using a randomised, single blind, test-retest intervention trial design. Each participant was given 1000 mg/d of elemental calcium (citrate) in tablet form for 4 weeks. They undertook a 25 mile bicycle ergometer time trial test at baseline (25TTB) and end of the intervention period (25TTC). A stationary electromagnetically braked ergometer (SRM ergometer; Schoberer Rad Messtechnik, Jülich, Germany) was used. Plasma NEFA concentration was determined using a NEFA C test kit (WAKO Chemicals GmbH, Neuss, Germany). Plasma NEFA was measured at rest, start and thereafter every 20 minutes till the end of the exercise. Descriptive data and all related analysis of significance were generated using PASW (Predictive Analytics SoftWare) Statistics Version 17 (SPSS Inc., Illinois, USA). Significance level was set at 95% confidence intervals (CI) (p < 0.05). Data are represented as measures of centrality and spread (mean ± standard deviation (SD). Main effect for time, main effect for trials and interaction between trials*time was used to detect statistical significance at each time point and across each trial respectively. Magnitudes of inferences were calculated using Cohen`s d. There was no statistically significant difference in appearance of NEFA in plasma between the two trials. However, the effect size of the changes in the plasma NEFA was large at the start of the exercise (d = 0.70) and moderate at rest (d = 0.46), 20 (d = 0.31), 40 (d = 0.30) and 60 (d = 0.47) min during exercise and small at the finish of the time trial (d = 0.07). The results indicate that calcium supplementation in well trained athletes may effect lipolysis during endurance exercise. A larger sample is needed to detect any statistically significant changes in the appearance of NEFA in the plasma if a recommendation to use calcium as an ergogenic aid in endurance sport is to be made.